Evolution of Global Lightning in the Transition From Cold to Warm Phase Preceding Two Super El Niño Events. Issue 3 (4th February 2021) - Williams, E.; Bozóki, T.; Sátori, G.; Price, C.; Steinbach, P.; Guha, A.; Liu, Y.; Beggan, C. D.; Neska, M.; Boldi, R.; Atkinson, M.
Abstract: Multistation observations of Schumann resonance (SR) intensity document common behavior in the evolution of continental‐scale lightning activity in two super El Niño events, occurring in 1997/98 and 2015/16. The vertical electric field component of SR at Nagycenk, Hungary and the two horizontal magnetic field components in Rhode Island, USA in 1997, and in 2014–2015, the two horizontal magnetic field components at Hornsund, Svalbard and Eskdalemuir, United Kingdom as well as in Boulder Creek, California and Alberta, Canada exhibit considerable increases in SR intensity from some tens of percent up to a few hundred percents in the transition months preceding the two super El Niño events. The UT time distribution of anomalies in SR intensity indicates that in 1997 the lightning activity increases mainly in Southeast Asia, the Maritime Continent and India, i.e. the Asian chimney region. On the other hand, a global response in lightning is indicated by the anomalies in SR intensity in 2014 and 2015. SR‐based results are strengthened by comparison to independent lightning observations from the Optical Transient Detector and the World Wide Lightning Location Network, which also exhibit increased lightning activity in the transition months. The increased lightning is attributable to increased instability due to thermodynamic disequilibrium between the surface and the midtroposphere during the transition. The main conclusion is that variations in SR intensity may act as a precursor for the occurrence and magnitude of these extreme climate events, and in keeping with earlier findings, as a precursor to maxima in global surface air temperature. Plain Language Summary: Schumann resonance (SR) is a global phenomenon produced by low frequency electromagnetic radiation (<100 Hz) from worldwide lightning. Lightning strokes act as wideband electromagnetic antennas transmitting in this specific frequency band, and due to the extreme low attenuation of electromagnetic waves, their radiated signals can be observed anywhere on Earth. This phenomenon enables the monitoring of global lightning with just a very few (up to four in this study) observation sites around the globe. The main advantage of the SR‐based method is the expectation that all of the worldwide lightning contributes to the measured SR field, which means the absence of detection efficiency problems which are inherent with many other lightning detection methods. In this work, we use SR measurements to monitor changes in both regional and global lightning activity in connection with two extremely large magnitude, so called "super" El Niño events (1997/98 and 2015/16). Our conclusion is that SR intensity variations in the transition months preceding these two El Niño events indicate an important increase in lightning activity attributable to thermodynamic disequilibrium. We suggest that SR intensity variations might be applied in the future to predict the occurrence of these extreme climate events. Key Points: Schumann resonance intensities are analyzed from distant stations in connection with two super El Niño events Increased Schumann resonance intensity indicates enhanced lightning activity in the transition from cold to warm phase in both events Schumann resonance intensity may be a precursor for occurrence of super El Niño events and for maxima in global surface air temperature